2016
DOI: 10.1371/journal.pone.0165744
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude Integrated Electroencephalogram as a Prognostic Tool in Neonates with Hypoxic-Ischemic Encephalopathy: A Systematic Review

Abstract: IntroductionPerinatal management and prognostic value of clinical evaluation and diagnostic tools have changed with the generalization of therapeutic hypothermia (TH) in infants with hypoxic-ischemic encephalopathy (HIE)Aimto ascertain the prognostic value of amplitude integrated electroencephalogram (aEEG) in neonates with HIE considering hours of life and treatment with TH.MethodsA systematic review was performed. Inclusion criteria were studies including data of neonates with HIE, treated or not with TH, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 38 publications
0
37
0
6
Order By: Relevance
“…Amplitude-integrated electroencephalography (aEEG) is a method for continuous monitoring of cerebral function at the bedside (9,10). aEEG displays both a limited-channel EEG recording and a compressed aEEG tracing that allows evaluation of cerebral background activity pattern over time and facilitates screening for seizures.…”
Section: Introductionmentioning
confidence: 99%
“…Amplitude-integrated electroencephalography (aEEG) is a method for continuous monitoring of cerebral function at the bedside (9,10). aEEG displays both a limited-channel EEG recording and a compressed aEEG tracing that allows evaluation of cerebral background activity pattern over time and facilitates screening for seizures.…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation of an aEEG tracing includes three categories – the classification of the background pattern, the identification of sleep–wake cycling (SWC), and the identification of seizures – all of which depend upon the infant's gestational age and different pathophysiological conditions . Previous studies reported that continuous extremely low voltage, flat tracing, or burst suppression of aEEG background patterns is correlated with unfavorable neurological outcomes in asphyxiated neonates, and recurrent seizures and status epilepticus have been shown to be indicators of poor neurodevelopmental outcomes, while fully developed SWC has been shown to be a good prognostic indicator . In this study, we incorporated the above three individual categories of an aEEG recording in order to objectively and comprehensively evaluate the cerebral function of newborns with other injuries than just HIE in order to determine the prognostic certainty of aEEG.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, our current results reported the effects of different ventilation [145]. However, we could not perform aEEG recordings in our experiments, but we admit that it represents one of the most commonly used non-invasive monitoring devices of critically sick neonates [146].…”
Section: Discussionmentioning
confidence: 82%